2011
DOI: 10.1002/asia.201100050
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Activation of Alkyne and Thioamide Functionalities; Direct Catalytic Asymmetric Conjugate Addition of Terminal Alkynes to α,β‐Unsaturated Thioamides

Abstract: A detailed study of the direct catalytic asymmetric conjugate addition of terminal alkynes to α,β-unsaturated thioamides is described. A soft Lewis acid/hard Brønsted base cooperative catalyst, comprising [Cu(CH(3)CN)(4)]PF(6), bisphosphine ligand, and Li(OC(6)H(4)-p-OMe) simultaneously activated both substrates to compensate for the low reactivity of copper alkynylide. A series of control experiments revealed that the intermediate copper-thioamide enolate functioned as a Brønsted base to generate copper alkyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 141 publications
0
17
0
Order By: Relevance
“…Thus, a simple mesitylcopper/ 16 catalytic system emerged as the second‐generation catalyst for this transformation, in which mesitylcopper irreversibly deprotonated the terminal alkyne 3 to enter into the catalytic cycle with the concomitant generation of mesitylene. This catalytic cycle proceeded smoothly to produce the β‐alkynyl thioamides 17 with yields and enantioselectivities comparable to those observed with the first‐generation catalyst 21…”
Section: Thioamides As Electrophiles In Catalytic Asymmetric Coopementioning
confidence: 69%
See 1 more Smart Citation
“…Thus, a simple mesitylcopper/ 16 catalytic system emerged as the second‐generation catalyst for this transformation, in which mesitylcopper irreversibly deprotonated the terminal alkyne 3 to enter into the catalytic cycle with the concomitant generation of mesitylene. This catalytic cycle proceeded smoothly to produce the β‐alkynyl thioamides 17 with yields and enantioselectivities comparable to those observed with the first‐generation catalyst 21…”
Section: Thioamides As Electrophiles In Catalytic Asymmetric Coopementioning
confidence: 69%
“…In‐depth analysis of the proton transfer process in the catalytic cycle with the first‐generation catalyst [Cu(CH 3 CN) 4 ]PF 6 / 16 /Li(OC 6 H 4 ‐ p ‐OMe) revealed an intriguing clue toward refining the catalytic system (Scheme ) 21. In the catalytic cycle of the first‐generation catalyst, the Cu/ 16 complex and Li(OC 6 H 4 ‐ p ‐OMe) cooperatively deprotonated the terminal alkyne 3 to generate Cu‐alkynylide 19 with concomitant formation of HOC 6 H 4 ‐ p ‐OMe (Scheme , cycle A).…”
Section: Thioamides As Electrophiles In Catalytic Asymmetric Coopementioning
confidence: 99%
“…Our previous investigations revealed that a mesitylcopper/chiral bisphosphine catalyst forms an active copper nucleophile with the liberation of mesitylene 6b,d. An analogous catalytic cycle can be delineated for the conjugate addition of thiols 2 (Scheme ).…”
Section: Methodsmentioning
confidence: 95%
“…However, the latter, including a variety of monounsaturated fatty acids such as 9Z-palmitoleic acid (C16:1) and 9Z-oleic acid (C18:1) and polyunsaturated fatty acids such as 9Z,12Z-linoleic acid (C18:2) and 5,8,11-eicosatrienoic acid (C20:3), do not appear to be dependent on carbon chain length or the degree of saturation (44). Additionally, a series of synthetic agonists such as GW9508, AMG 837 and 3-substituted 3-(4-aryloxyaryl)propanoic acids have been recently reported (47)(48)(49)(50). Several synthetic GPR40 antagonists have also been well described, including DC260126 and GW1100 (51-54).…”
Section: Ligandsmentioning
confidence: 99%